2018
DOI: 10.1167/iovs.18-25087
|View full text |Cite
|
Sign up to set email alerts
|

Supernormal Flicker ERGs in Eyes With Central Retinal Vein Occlusion: Clinical Characteristics, Prognosis, and Effects of Anti-VEGF Agent

Abstract: PURPOSE. To determine the clinical characteristics, prognosis, and effect of anti-vascular endothelial growth factor (VEGF) agents on eyes with a central retinal vein occlusion (CRVO) with and without supernormal flicker ERG amplitudes. METHODS. Forty-eight eyes of 48 patients with a CRVO were studied. Flicker ERGs were recorded from fully dilated eyes with the RETeval system. The amplitudes and implicit times of the fundamental component were analyzed. ''Supernormal flicker ERGs'' were defined as those whose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…One surprising finding was the larger than baseline b-wave amplitudes at 2 days, termed "supernormal ERGs" in the earliest observations of large scotopic b-waves 37,51 , primarily in the ROCK-inhibitortreated eyes. Although increase in ERG amplitudes is uncommon among visual disorders, such observations have been reported in patients with cone dystrophies 37,51,52 , early diabetic retinopathy 53 , central retinal vein occlusion (CRVO) 54,55 and in animal disease models, e.g., Ant1-deficient mice 56 , a rabbit model of retinal degeneration 57 , and a rat traumatic brain injury model 58 . In normal porcine retina, intravitreal injection of AR13503 alone did not cause increased scotopic ERG responses after 7 days (n = 3 animals, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One surprising finding was the larger than baseline b-wave amplitudes at 2 days, termed "supernormal ERGs" in the earliest observations of large scotopic b-waves 37,51 , primarily in the ROCK-inhibitortreated eyes. Although increase in ERG amplitudes is uncommon among visual disorders, such observations have been reported in patients with cone dystrophies 37,51,52 , early diabetic retinopathy 53 , central retinal vein occlusion (CRVO) 54,55 and in animal disease models, e.g., Ant1-deficient mice 56 , a rabbit model of retinal degeneration 57 , and a rat traumatic brain injury model 58 . In normal porcine retina, intravitreal injection of AR13503 alone did not cause increased scotopic ERG responses after 7 days (n = 3 animals, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…However, work in patients is encouraging. Miyata et al 55 suggested that after anti-VEGF treatment of non-ischemic CRVO, eyes with supernormal ERGs had a better prognosis after 1 year than non-ischemic CRVO eyes without supernormal ERG amplitudes.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, hyperactivity in ERG responses is observed in central retinal vein occlusion [63], and the estimated mechanism involves ischemia-related increase in the local levels of inflammatory cytokines [64]. Given that AQP4 is important for water diffusion allowing bidirectional water transport across the plasma membrane [3, 12], the fine-tuning of diffusible factor concentrations, besides glutamate and potassium, at the neuron-glial site could be also involved in its role in preserving neuron-microenvironment homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Full-field flicker ERGs were recorded with the RETeval system as described. 35 After full mydriasis with topical 0.5% tropicamide and 0.5% phenylephrine HCl, (Mydrin-P; Santen Pharmaceutical Co., Ltd., Osaka, Japan), the flicker ERGs were recorded. A special skin electrode array (Sensor Strip; LKC Technologies, Inc., Gaithersburg, MD, USA) was placed 2 mm from the margin of the lower eyelid.…”
Section: Full-field Electroretinography (Erg)mentioning
confidence: 99%